Manajemen Pengembangan Dakwah pada Yayasan Daarul Armina Kota Bengkulu - Ahmad Rafiezal Maizan; Wildan Yahya; Asep Ahmad Siddiq (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. As a da'wah institution, the foundation must have good management in carrying out da'wah development. This can maximize the development of da'wah at the foundation. This research is entitled "Management of Da'wah Development at the Daarul Armina Foundation, Bengkulu City". This research aims to find out how Da'wah Development Management is implemented at the Daarul Armina Foundation. This type of research is qualitative, with descriptive-analytical methods, and uses Henri Fayol's (1916) theory of management functions: planning, organizing, commending, coordinating and controlling. The results of the research show that the management of da'wah development at the Daarul Armina Foundation consists of planning, organizing, commending, coordinating and controlling. However, this management has not been implemented optimally, especially in planning, organizing and monitoring. Abstrak. Sebagai sebuah lembaga dakwah, yayasan harus memiliki manajemen yang baik dalam menjalankan pengembangan dakwah. Hal tersebut bisa memaksimalkan pengembangan dakwah pada yayasan. Penelitian ini berjudul “Manajemen Pengembangan Dakwah pada Yayasan Daarul Armina Kota Bengkulu”. Penelitian ini bertujuan untuk mengetahui bagaiman Manajemen Pengembangan Dakwah yang diterapkan pada Yayasan Daarul Armina. Jenis penelitian ini adalah kualitatif, dengan metode deskriptif-analisis, serta menggunakan teori fungsi manajemen Henri Fayol (1916) perencanaan (planning), pengorganisasian (organizing), commending (pengarahan), coordinating (pengkoordinasian), dan controlling (pengawasan). Hasil penelitian menunjukkan bahwa manajemen pengembangan dakwah pada yayasan daarul armina terdiri dari perencanaan (planning), pengorganisasian (organizing), commending (pengarahan), coordinating (pengkoordinasian), dan controlling (pengawasan). Akan tetapi manajemen tersebut belum dilaksanakan secara optimal terutama dalam perencanaan, pengorganisasian, dan pengawasan.